SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JENIS ANJING RAS MENGGUNAKAN PEMODELAN AHP - , Phie Chyan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research has produced an application as a tool for Decision Support System that can assist in decision making with the ability to analyse compabilty assesment of dog breeds respect to its adopters. This Decision support system use Analytic Hiearachy Process (AHP) modelling which each criterions was based on dog breeds atrributes. The Process of Using AHP model is a). make pairwise comparison matrix, b). Calculate priority value for each criterion, c). make pairwise matrix of subcriteion respected to its criterion, d). Calculate the priority value of each subcriterion and form calculation using AHP. Combination between criterion, subcriterion, intensity, and value entered with official dog breeds data from the federation of cynology will able the application to generate ranking of each dog breeds based on compability to its adopterâs preferences. This ranking can be use as basis of recommendation for decision maker to choose what kind of breeds that match with their preference and needs. This Application software is web based and using PHP as its programming langueage and Apache as a webserver to running it.